THE ROLE OF ARTIFICIAL INTELLIGENCE IN PERSONALIZING DIGITAL MARKETING AND CUSTOMER EXPERIENCE - Siti Nurhayati; Yenni Kurnia Gusti; Tri Apriyono (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study aims to examine the role of Artificial Intelligence (AI) in personalizing digital marketing and enhancing customer experience through a literature review approach. The research employs a qualitative method by analyzing various academic journals, books, and scholarly publications related to AI technologies, digital marketing strategies, and customer experience management. The findings indicate that AI plays a significant role in improving marketing personalization through technologies such as machine learning, predictive analytics, recommendation systems, and natural language processing. These technologies enable organizations to analyze customer behavior, predict preferences, and deliver personalized content and services in real time. The study also reveals that AI enhances customer experience by improving responsiveness, efficiency, and customer engagement across multiple digital platforms. However, the implementation of AI also presents several challenges, including data privacy concerns, ethical issues, algorithmic bias, and organizational readiness. Therefore, businesses must adopt responsible AI governance and balance technological innovation with customer trust and data protection. Overall, this research concludes that AI has transformed digital marketing practices and customer experience management by enabling more customer-centered and data-driven business strategies in the digital era.